ChemInform Abstract: Application of a Mild Hydrothermal Approach Containing an in situ Reduction Step to the Growth of Single Crystals of the Quaternary U(IV)‐Containing Fluorides Na4MU6F30 (M: Mn2+, Co2+, Ni2+, Cu2+, and Zn2+) Crystal Growth, Structures, and Magnetic Properties. Issue 26 (1st July 2014) - Yeon, Jeongho; Smith, Mark D.; Tapp, Joshua; Moeller, Angela; zur Loye, Hans‐Conrad
Abstract Single crystals of the title compounds are hydrothermally prepared from aqueous mixtures of UO2(OAc)2, NaF, HF, and MCl2 (M: Mn, Co, Ni, Zn) or Cu(OAc)2 (autoclave, 200 °C, 1 d, 20, 70, 60, 80, and about 100% yield for Mn‐, Co‐, Ni‐, Zn‐, and Cu‐containing materials, respectively).